Incorporation and distribution of noble metal atoms in polyacrylonitrile colloidal particles using different polymerization strategies. (6th June 2018) - Beltzung, Anna; Colombo, Claudio; Nachtegaal, Maarten; Wu, Hua; Storti, Giuseppe; Morbidelli, Massimo
Abstract: This work is focused on the incorporation of inorganic compounds into an organic framework. More precisely, noble metals are being incorporated in-situ in polyacrylonitrile colloidal particles (CPs) using, scalable and reproducible synthesis routes. For this purpose, oil-soluble platinum- and palladium-based precursors are used for physical entrapment based on mini-emulsion polymerization, while water soluble precursors of the same metals are used for the incorporation via chemical entrapment based on conventional emulsion polymerization. For the latter, it is shown that one can well alter the spatial distribution of the metal within the CPs by tuning the feeding strategy of the precursor. In addition, chemical entrapment requires the complexation of the metal with acrylonitrile, thus resulting in the incorporation of single atoms and dimers, as suggested by both X-ray absorption spectroscopy and indirectly by NMR-titration. The visualization of the extent of incorporation was performed by STEM-EDX on all synthesized CPs, while ICP-OES was applied for a quantitative evaluation. Graphical abstract: Image 1 Highlights: Reproducible incorporation of Pt or Pd atoms inside polymer particles (PPs). Physical entrapment of Pt atoms through mini-emulsion polymerization. Chemical entrapment of Pt or Pd atoms through emulsion polymerization. Different synthesis procedures lead to different distributions of Pt or Pd in PPs.